Breast Cancer Brain Metastasis: The Potential Role of MRI Beyond Current Clinical Applications - Hadjipanteli, Andria; Doolan, Paul; Kyriacou, Efthyvoulos C.; Constantinidou, Anastasia (My University, 2020)
Breast cancer brain metastasis (BCBM) represents a major clinical challenge. Can MRI help in advancements in the management of BCBM? This review discusses MRI developments and the corresponding potential advancements in BCBM management.
Keywords: breast cancer brain metastasis; Breast cancer management; Magnetic resonance imaging